Cytokine responses to Schistosoma mansoni and Schistosoma haematobium in relation to infection in a co-endemic focus in northern Senegal. - Lynn Meurs; Moustapha Mbow; Nele Boon; Kim Vereecken; Abena Serwaa Amoah; Lucja A Labuda; Tandakha Ndiaye Dièye; Souleymane Mboup; Maria Yazdanbakhsh; Katja Polman (Public Library of Science (PLoS), 2014)
In Africa, many areas are co-endemic for the two major Schistosoma species, S. mansoni and S. haematobium. Epidemiological studies have suggested that host immunological factors may play an important role in co-endemic areas. As yet, little is known about differences in host immune responses and possible immunological interactions between S. mansoni and S. haematobium in humans. The aim of this study was to analyze host cytokine responses to antigens from either species in a population from a co-endemic focus, and relate these to S. mansoni and S. haematobium infection.Whole blood cytokine responses were investigated in a population in the north of Senegal (n = 200). Blood was stimulated for 72 h with schistosomal egg and adult worm antigens of either Schistosoma species. IL-10, IL-5, IFN-γ, TNF-α, and IL-2 production was determined in culture supernatants. A multivariate (i.e. multi-response) approach was used to allow a joint analysis of all cytokines in relation to Schistosoma infection.Schistosoma haematobium egg and worm antigens induced higher cytokine production, suggesting that S. haematobium may be more immunogenic than S. mansoni. However, both infections were strongly associated with similar, modified Th2 cytokine profiles.This study is the first to compare S. mansoni and S. haematobium cytokine responses in one population residing in a co-endemic area. These findings are in line with previous epidemiological studies that also suggested S. haematobium egg and worm stages to be more immunogenic than those of S. mansoni.